Building Condition Assessment (BCA) on school building in Sabah, Malaysia. Issue 1 (May 2020) - Noor, Syahirah Mohd; Richard, Hazel Kiddo; Ibrahim, Izni Syahrizal; Sarbini, Noor Nabilah; Hanseung, Lee; Kumar, Jitendra
Abstract: The standard guideline for Building Condition Assessment (BCA) [7] has been introduced by Public Work Department of Malaysia to manage the government's building in Malaysia especially in Peninsular Malaysia. Whereby, BCA has never been implemented in Public Work Department of Sabah. Since there is so many buildings need to be maintained especially existing school building, it is the right time to introduce a systematic assessment method for managing the maintenance work. Visual inspections for the selected building have been done with reference to Standard guideline for Building Condition Assessment (BCA) [7] by Public Work Department of Malaysia. Building Condition Assessment online system (BCA-OS) by Universiti Teknologi Malaysia Forensic Centre was used to analyse the existing physical condition of the building in order to determine the rating of the buildings. By using this system, the building wil1 be rated 1 (good) to 5 (critical). Material testing will be conducted to building with rating 3, 4 and 5. This paper will discussed the results obtained from Building Condition Assessment online system (BCA-OS) and test result on 2 blocks of a school in Sabah. In this study it is found that Building Condition Assessment online system are convenient to use and useful to rate the actual physical condition of the existing building. The rating from BCA-OS was found to be really representing the actual condition observed from visual inspection.